1968
DOI: 10.1038/bjc.1968.41
|View full text |Cite
|
Sign up to set email alerts
|

A study of soluble protein and sulfhydryl levels in the rat liver during rapid normal and premalignant growth

Abstract: FOLLOWING the demonstration by Miller and Miller (1947) and Miller, Miller, Sapp and Weber (1949) that carcinogenic azo dyes are bound covalently to rat liver proteins before the appearance of tumors, the cytoplasmic h protein components of this combination (Sorof and Cohen, 1951; Wirtz and Arcos, 1958) have been extensively investigated. During liver carcinogenesis by the aminoazo dyes and by 2-acetylaminofluorene, the h2 liver proteins contain the greatest portion of the soluble carcinogen-protein conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
1989
1989

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Hence all tissues were homogenized in the presence of chloride ion which in boundary electrophoresis, as stressed by S o r o f et al [10] improves the resolution of h proteins and protects them from pre cipitation and denaturation. In a recent report [2] this point has not been observed and this possibly accounts for their equivocal findings in the case of regenerating rat liver. Repeated observations have shown that the pattern of the electrophoretic profiles of both normal and regenerating rat liver at pH 8.6 is constant and that the ratios of the quantities of protein in each band remain within very narrow limits (Tab.…”
Section: Discussionmentioning
confidence: 83%
“…Hence all tissues were homogenized in the presence of chloride ion which in boundary electrophoresis, as stressed by S o r o f et al [10] improves the resolution of h proteins and protects them from pre cipitation and denaturation. In a recent report [2] this point has not been observed and this possibly accounts for their equivocal findings in the case of regenerating rat liver. Repeated observations have shown that the pattern of the electrophoretic profiles of both normal and regenerating rat liver at pH 8.6 is constant and that the ratios of the quantities of protein in each band remain within very narrow limits (Tab.…”
Section: Discussionmentioning
confidence: 83%